2019
DOI: 10.4103/ijo.ijo_364_19
|View full text |Cite
|
Sign up to set email alerts
|

Newer indices for predicting macular hole closure in idiopathic macular holes: A retrospective, comparative study

Abstract: Purpose:To study the utility and predictive ability of newer macular hole (MH) indices for closure following surgery.Methods:In this retrospective study, pre- and post-operative optical coherence tomography images of 49 eyes with idiopathic full-thickness MH were reviewed and analysed. Various quantitative parameters of MH like maximum outer diameter (OD), minimum diameter between edges, height, nasal and temporal arm lengths, macular hole angle were noted. Indices including hole form factor, Macular Hole Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 10 publications
2
45
1
Order By: Relevance
“…22,23 The determination of the macular hole index as was obtained in this study are of easy application, therefore, the better outcome of the surgical procedure can be pre-operatively determined. The functional results found in this study are comparable to those of literature, 24,25 showing that MHI is a good predictive factor for FTMH surgery outcome. We did not find any correlation between gender and age with the outcome of macular hole surgery.…”
Section: Discussionsupporting
confidence: 88%
“…22,23 The determination of the macular hole index as was obtained in this study are of easy application, therefore, the better outcome of the surgical procedure can be pre-operatively determined. The functional results found in this study are comparable to those of literature, 24,25 showing that MHI is a good predictive factor for FTMH surgery outcome. We did not find any correlation between gender and age with the outcome of macular hole surgery.…”
Section: Discussionsupporting
confidence: 88%
“…This findings are in line with the result of this study which found that those who waits ≤ 6 months had better outcome than ≥6 months at 68.8% and 31.2% respectively. Furthermore, according to Venkatesh et al 32 The duration of onset under 6 months is one of the functional success factors, namely a better improvement in VA after the closure of MH. 5,21,22 In MH that has occurred for more than 2-3 years, the reported success rate is lower (63%) and visual acuity is worse than early MH.…”
Section: Discussionmentioning
confidence: 99%
“…For example, THI is a ratio between maximum height to minimum hole diameter and accounts for antero-posterior traction where DHI signifies tangential traction on hole by evaluating the ratio of minimum hole diameter and base diameter. 14 Other indices like MHI and HFF can take into account both tangential and antero-posterior tractional forces in their calculations. Tractional Hole index has been positively co related with better visual outcomes at 3 months after macular hole surgery.…”
Section: Introductionmentioning
confidence: 99%